Krygshelde/War Heroes: Sersant Quentin George Murray Smythe - 'n Man van durf en daad. - Kroukamp, W. (Scientia Militaria - South African Journal of Military Studies, 2012)
There have been dozens of almost unbelievable acts of courage in every war. Few can excel the incredible exploit of Sergeant Q.G.M. Smythe, who single-handed, destroyed a German anti-tank gun position and captured its crew.